Gender differences in psychiatric comorbidity and personality characteristics among adults seeking treatment for problematic internet use - Machado, Rodrigo Menezes; Kim, Hyoun S.; Oliveira de Andrade, Vinicius; Snaychuk, Lindsey A.; Moura, Carla Cavalheiro; Belliero Martini, Cornelia; de Abreu, Cristiano Ricardo Faedo Nabuco; Hodgins, David C.; Tavares, Hermano (Frontiers in Psychiatry, 2022)
In the present study, we investigated gender differences in personality and psychiatric correlates among adults (N=115) seeking treatment for Problematic Internet Use (PIU) at a specialized clinic in São Paulo, Brazil. All participants were assessed at the beginning of their treatment for co-occurring psychiatric conditions, other addictive behaviors, and personality characteristics. Women (n=20) were more likely to present with greater rates of psychiatric comorbidity compared to men (n=95), including mood disorders, anxiety disorders, obsessive compulsive disorder, post-traumatic stress disorder, and bulimia nervosa. Women also had a greater severity of certain behavioral addictions, such as compulsive buying and disordered eating. Gender differences were also found across personality characteristics, with women scoring higher on impulsivity, novelty seeking, and self-transcendence compared to men. To our knowledge, the present study is the first to investigate gender differences for PIU in a clinical sample. The results suggest that there are notable gender differences in individuals seeking treatment for PIU which underscores the importance of assessing for co-occurring conditions, especially in women. Understanding the characteristics associated with PIU can help serve to inform the most appropriate interventions to bolster treatment outcomes.